2001
DOI: 10.1023/a:1013107732572
|View full text |Cite
|
Sign up to set email alerts
|

Localised disease in cancer of unknown primary (CUP): The value of positron emission tomography (PET) for individual therapeutic management

Abstract: In CUP patients, PET has a certain impact on detection of the primary as well as of the disseminated disease. and may also have a certain impact on therapeutic management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 18 publications
1
51
0
9
Order By: Relevance
“…Nevertheless, there remains a core of patients for whom the primary is uncertain. Rades et al (2001) reported that PET allowed detection of the primary site in 43% (18 out of 42 patients) of the study population that included only localised CUP based on conventional staging procedures. Dissemination was detected by PET in 38%, and in 69%, the PET result influenced the selection of the definitive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there remains a core of patients for whom the primary is uncertain. Rades et al (2001) reported that PET allowed detection of the primary site in 43% (18 out of 42 patients) of the study population that included only localised CUP based on conventional staging procedures. Dissemination was detected by PET in 38%, and in 69%, the PET result influenced the selection of the definitive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…7,[9][10][11][12][13][14][15][16][17][18][19][20] These figures, however, were reported in series that included patients with CUP and extracervical metastases as well as varying cancer types, for example, SCC, adenocarcinoma, melanoma, large cell carcinoma, plasmocytoma, etc., and the diagnostic performance of FDG-PET was not determined separately for cervical versus extracervical CUP presentations and as a function of the histological subtype. Further, in several of these studies, the PET methodology was either not standardized or inadequate and most of these studies were conducted using FDG-PET and not FDG-PET/CT, which might have resulted in a higher rate of false-positive findings and sensitivity.…”
mentioning
confidence: 99%
“…PET (positron emission tomography) with the use of 18-fluorodeoxyglucose in combination with the CT examination is considered by many authors as the method of high efficacy, both in the determination of the primary lesion (40-60%), and staging of the neoplastic process (26,27,28). Greven et al pointed to the limited specificity of 18-FDG PET: the primary lesion was diagnosed in 1 of 13 analysed cases with a high percentage of false positive results (29).…”
Section: Discussionmentioning
confidence: 99%